2022
DOI: 10.1007/s11852-022-00916-w
|View full text |Cite
|
Sign up to set email alerts
|

Flash flooding hazard assessment, modeling, and management in the coastal zone of Ras Ghareb City, Gulf of Suez, Egypt

Abstract: The assessment of flash flood hazards in the coastal zone of Ras Ghareb City (RGC), Red Sea, Egypt, was accomplished through the use of GIS tools and the spatial multi-criteria approach. The presented work aims to assess, integrate, and generate potential flash flood hazard maps. The analytic hierarchy process was utilized to calculate weights of hazard and vulnerability of flash flood controlling factors and their parameters such as topographical, geological, and hydrological factors. In addition, the risk de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…DEMs are a commonly used data type for mapping large-scale movements, faults, floods, and topography of coastal areas [25]. In flash flood studies, DEMs are considered a valuable data source for obtaining information on various fundamental parameters of the terrain [26]. Moustafa et al used a DEM reflecting regional surface conditions when mapping the sensitivity of fault segments within the Egyptian continent (possible fault zone maps) [14].…”
Section: Remote Sensing Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…DEMs are a commonly used data type for mapping large-scale movements, faults, floods, and topography of coastal areas [25]. In flash flood studies, DEMs are considered a valuable data source for obtaining information on various fundamental parameters of the terrain [26]. Moustafa et al used a DEM reflecting regional surface conditions when mapping the sensitivity of fault segments within the Egyptian continent (possible fault zone maps) [14].…”
Section: Remote Sensing Image Processingmentioning
confidence: 99%
“…They used the trained back-propagation weights to calculate the landslide susceptibility index (LSI) [38].In order to identify the key factors contributing to landslide hazards, Lin et al used the CF method to analyze eight geoenvironmental factors in the area [39]. After completing experiments to assess flash flood outbreaks, Arnous et al concluded that an enhanced understanding of the mechanisms of interaction between topographic features and extreme meteorological conditions could lead to a better understanding of the causes of flood outbreaks [26]. Ali et al concluded that there are three primary conditions for the origin of a mudslide: slope, water source, and erodible unconsolidated sediments, which can be used as a vital source of evaluation factors for assessing mudslide hazards [40].…”
Section: Selection and Identification Of Evaluation Factorsmentioning
confidence: 99%
“…Gebel Akheider and downstream of Wadi Akheider 3. Gebel El-Ramliya and downstream of Wadi El-Noqra Based on the weighted basin and channel geomorphometric parameters (circularity, basin length, basin area, basin perimeter, bifurcation ratio, drainage density, and stream frequency), the Wadi Beda Main Basin was given a moderate rank of flood potentiality (Arnous et al 2022). This moderate rank indicates that Wadi Beda Main Basin is not capable to collect high quantity of runoff water, and hence, a low quantity of water moves out the basin, which is lowrisk Basin.…”
Section: The Integrated Thematic Mapmentioning
confidence: 99%
“…Selected criteria (Choudhury et al, 2022) (1) elevation, (2) aspect, (3) curvature, (4) slope, (5) land cover, ( 6) and ( 7) normalised difference vegetation/water index (NDVI) (NDWI), (8) distance to roads, (9) distance to rivers, (10) Rainfall, (11) TPI, and ( 12) TWI (Serdar et al, 2022) (1) slope, (2) groundwater depth, (3) distance to streams, and (4) land use/land cover (LULC) (Arnous et al, 2022) (1) morphometric variables, (2) runoff characteristics, (3) units of lithology, (4) slope, (5) elevation, (6) structure lineament, and (7) rainfall volume (Msabi et al, 2021) (1) geology, (2) accumulation of flow, (3) slope, (4) LULC, (5) density of drainage, (6) stream order, (7) elevation, and (8) soil It is crucial to keep in mind that various factors have varying roles depending on the local natural conditions in each location (Mudashiru et al, 2021;Yaseen et al, 2022). For example, the study area is a dry, sand-dominated desert.…”
Section: Studymentioning
confidence: 99%
“…A simplified statistical technique is used to estimate peak discharge and peak time based on the correlation between parameter values and runoff likelihood (Pradhan et al 2010). We applied the same procedures as in the first criterion to define the flood susceptibility using cumulative runoff parameters, where the surface velocity, peak discharge, and time concentration characteristics are categorised into five groups based on risk degree probability (Arnous et al, 2022) (Fig. 12).…”
Section: -2 Surface Runoff Potentiality Mappingmentioning
confidence: 99%